The return of Foreign Terrorist Fighters and the security of the EU - Lopes, J. (EGA - Europe As a Global Actor, 2019)
At the global level, it is estimated that 40.000 people have been radicalised to fight in Syria and Iraq (2017). According to EUROPOL, more than 1.000 have returned to Europe. This communication aims to understand the possible consequences of the return of the foreign terrorist fighters to the European Union (EU). Drawing upon an explanative approach, we argue that the returnees constitute a potential security threat to the EU because they are in possession of certain capabilities (e.g. battlefield experiences and connection to terrorist networks) which can be used for various ends as recruitment or the perpetration of terrorist attacks. The military defeat of Daesh did not diminish the threat of terrorism in European territory and the fight against radicalisation remains and it will likely be, in the longer run, one of the main keystones of counterterrorism in Europe.